Genetic parameters of Eucalyptus spp. clones in northeastern Brazil - Furlan, Rodrigo de Andrade [UNESP]; Moraes, Cristiano Bueno de; Tambarussi, Evandro Vagner [UNESP] (Universidade Federal do Paraná, 2020)
Brazil is the largest charcoal producers in the world, with the main centers of charcoal consumption located in the states of Minas Gerais, Mato Grosso do Sul, Espírito Santo, Maranhão, and Pará. Planting of Eucalyptus in the northern and northeastern states of Brazil is relatively new and is limited the lack of genetic materials adapted to the region's high temperatures and severe, prolonged periods of drought. The objective of this study was to assess the genetic parameters and variability and determine the genotype x environment interaction for drought tolerance in Eucalyptus clonal tests established in two environments in the municipality of Grajaú, Maranhão State, Brazil. The tests were planted in January 2011 in clayey and sandy soils in a randomized complete block design with 130 clones, one plant per plot, and 20 replicates. The studied clones showed high genetic variability for drought tolerance, with coefficients of relative variance (CVr) consistently greater than 0.8 for DBH and volume. This indicates high levels of genetic control and less influence of environmental factors on the phenotype, which allows for selection and obtaining gains through breeding. Heritability estimates were high for growth traits, with average clone heritabilities (ĥ2m) greater than 0.85, as well as acuracies (raa) above 0.9 for DBH and volume in clone selection. There was a simple interaction between genotype x environment for the clones under the two different soil conditions.
Keywords: Clone silviculture; Drought tolerance; Eucalyptus spp; Forest breeding; Genetic analysis